2017
DOI: 10.3390/f8110446
|View full text |Cite
|
Sign up to set email alerts
|

Using Linear Mixed-Effects Models with Quantile Regression to Simulate the Crown Profile of Planted Pinus sylvestris var. Mongolica Trees

Abstract: Abstract:Crown profile is mostly related to the competition of individual trees in the stands, light interception, growth, and yield of trees. A total of 76 sample trees with a total number of 889 whorls and 3658 live branches were used to develop the outer crown profile model of the planted Pinus sylvestris var. mongolica trees in Heilongjiang Province, China. The power-exponential equation, modified Kozak equation, and simple polynomial equation were used and the model which showed the best performance was u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 47 publications
1
13
0
Order By: Relevance
“…Among trees of the same age, trees with a large DBH are more dominant, more competitive, and intercept more light, and they therefore grow better. It is clear from these results that the effect of tree growth on crown shape is consistent with the results of the study by Sun et al [ 8 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Among trees of the same age, trees with a large DBH are more dominant, more competitive, and intercept more light, and they therefore grow better. It is clear from these results that the effect of tree growth on crown shape is consistent with the results of the study by Sun et al [ 8 ].…”
Section: Discussionsupporting
confidence: 92%
“…The parabola equation is the equation most widely used to describe the outer crown profile due to its flexibility [ 5 , 8 , 49 ], and its reparameterized form is shown below as Equation (1). where OR is the outer crown radius; RDINC is the relative depth into the crown; LCR is the largest crown radius; and , , and are parameters to be estimated.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…For this reason, a number of covariates at tree and at stand level were added to increase the percentage of crown variation that could be explained by the model. Basal area, as a measure of stand density, is expected to affect crown width [59], while the canopy base height has been mentioned as a valid predictor of crown width by a number of relevant studies [31][32][33][34]. Tree height has also been used as a valid regressor of crown width allometry at tree level [31,32], while both the RSI and the fraction between diameter and quadratic mean diameter have been found to affect crown width variation according to Ducey [29].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that the crown diameter of Mongolian pine increased with both age and stand density [65]. As crowns may overlap, competition is a crucial factor that affects Mongolian pine growth [66]; thus, trees growing in a dense forest may undergo decline more readily.…”
Section: Vulnerability To Droughtmentioning
confidence: 98%